2008
DOI: 10.1590/s0034-89102008000800007
|View full text |Cite
|
Sign up to set email alerts
|

Idade e uso de preservativo na iniciação sexual de adolescentes brasileiros

Abstract: RESULTS:In 2005, 61.6% of young interviewees had practiced sex and the average age for fi rst intercourse was 14.9, with no signifi cant difference to young interviewees in 1998. Condom use during fi rst sexual intercourse increased signifi cantly in both stable relationships (48.5% in 1998 vs. 67.7% in 2005) and casual relationships (47.2% in 1998 vs. 62.6% in 2005) across almost all segments. There were differences by gender, skin color and schooling for both age of fi rst sexual intercourse and condom use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
41
3
85

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(140 citation statements)
references
References 19 publications
11
41
3
85
Order By: Relevance
“…According to data from 2008, adolescents who reported having more sexual partners in general had high knowledge about how to prevent STDs and mentioned a more frequent use of condoms, compared to other age groups. This last result was similar to that found by Paiva et al (2008) 1 , who also assessed national data from the study entitled "Comportamento Sexual e Percepções da População Brasileira Sobre HIV/Aids" (Sexual Behavior and Perceptions of HIV/ AIDS among the Brazilian Population), conducted between 1998 and 2005. However, when comparing the results of the latter study* from 1998 with the 2008 PCAP information about the use of male condoms in the first sexual intercourse in adolescents aged 15-24 years, the prevalence of such use increased from 52.8% to 60.9%, thus showing that this practice is still low among adolescents**.…”
Section: Introductionsupporting
confidence: 87%
“…According to data from 2008, adolescents who reported having more sexual partners in general had high knowledge about how to prevent STDs and mentioned a more frequent use of condoms, compared to other age groups. This last result was similar to that found by Paiva et al (2008) 1 , who also assessed national data from the study entitled "Comportamento Sexual e Percepções da População Brasileira Sobre HIV/Aids" (Sexual Behavior and Perceptions of HIV/ AIDS among the Brazilian Population), conducted between 1998 and 2005. However, when comparing the results of the latter study* from 1998 with the 2008 PCAP information about the use of male condoms in the first sexual intercourse in adolescents aged 15-24 years, the prevalence of such use increased from 52.8% to 60.9%, thus showing that this practice is still low among adolescents**.…”
Section: Introductionsupporting
confidence: 87%
“…Access to better education, better living conditions and greater opportunity would favor increased options during youth trajectories. 8,10,13 In the absence of these structural and infl uencing conditions, pregnancy, although unplanned, constitutes a life plan and not an absence of planning, as found in the present study.…”
Section: Discussionsupporting
confidence: 55%
“…Studies that explore this behavior have observed the same relationship. 8,10,13 Sexual and reproductive behaviors appear to be infl uenced by structural opportunities and by cultural norms. Poorer and less educated women had a lower percentage The results on sources for contraception show that women of lower social status have a greater dependency on the Public Health System (SUS) in order to meet their reproductive rights.…”
Section: Discussionmentioning
confidence: 99%
“…Conforme pode ser observado na Tabela 1, a maioria das adolescentes afirmou ter vida sexual ativa, corroborando dados apresentados na literatura que caracterizam o início da vida sexual entre os 15 e 19 anos (Paiva, Calazans, Venturi, & Dias, 2008 Verificou-se nas mulheres de meia-idade um dado preocupante e que merece atenção que são as dificuldades apresentadas por elas, principalmente considerando que as mesmas influenciam na relação dessas mulheres. Portanto, surge também a necessidade de se investigar se essas dificuldades estão de alguma forma relacionada com a insatisfação da relação sexual, representada por 50% das mulheres, uma vez que a mulher na meia-idade está vivenciando o período de climatério, que é a transição do período reprodutivo para um não reprodutivo.…”
Section: Práticas Sexuaisunclassified